Politeness principle Analysis In Javanese Daily Conversation - Buntara Adi Purwanto; Shonu Shams (Metaphor, 2020)
Politeness has an important role in javanesse society. The norm of politeness stands in the highest level of javanesse society. There are many unwritten norms which people apply it in their daily life, especially in a conversation. Therefore, the purpose of this study is to describe and explain the use of politeness in javanesse daily conversation and understanding the politeness used in relation with the background culture and situation when the conversation happened. It can be found in this study that javanesse politeness use indirect speech, especially when people accept an offer. In relation with Leech’s maxim, Javanesse people tend to use the maxim of modesty. In this case they will minimize the prise to self, especially whan they are talking about what they have and what they do.